2012
DOI: 10.1016/j.cortex.2011.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Asyntactic comprehension, working memory, and acute ischemia in Broca’s area versus angular gyrus

Abstract: We evaluated sentence comprehension of variety of sentence constructions and components of short term memory in 53 individuals with acute ischemic stroke, to test some current hypotheses about the role of Broca's area in these tasks. We found that some patients show structure-specific, task-independent deficits in sentence comprehension, with chance level of accuracy on passive reversible sentences, more impaired comprehension of object-cleft than subject-cleft sentences, and more impaired comprehension of rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 38 publications
2
33
1
3
Order By: Relevance
“…Language studies have further demonstrated that stroke-induced lesions of the angular gyrus (overlapping our cluster 2) impaired processing of passive reversible sentences (e.g., “the niece was kicked by the father”) and complex object cleft constructions (e.g., “It was the niece that the father kicked”) (Newhart et al, 2011). This suggests a role of the angular gyrus in complex working memory and syntax.…”
Section: Discussionmentioning
confidence: 98%
“…Language studies have further demonstrated that stroke-induced lesions of the angular gyrus (overlapping our cluster 2) impaired processing of passive reversible sentences (e.g., “the niece was kicked by the father”) and complex object cleft constructions (e.g., “It was the niece that the father kicked”) (Newhart et al, 2011). This suggests a role of the angular gyrus in complex working memory and syntax.…”
Section: Discussionmentioning
confidence: 98%
“…This is challenging from a practical standpoint, and also because there are often other factors at play early after a brain injury, such as edema and hypoperfusion, that may complicate the picture in different ways. However, several lesion-symptom mapping studies have successfully demonstrated specific regions associated with various component processes of spoken language understanding in acute stroke patients (Kümmerer et al, 2013; Newhart, Ken, Kleinman, Heidler-Gary, & Hillis 2007; Newhart et al, 2012; Race, Ochfeld, Leigh, & Hillis, 2012; Rogalsky, Pitz, Hillis, & Hickok, 2008; Tsapkini, Frangakis, & Hillis, 2011) or resective surgery patients in the immediate post-operative period (Wilson et al, 2015). …”
Section: Challenges and Solutions For Studying Spoken Languagementioning
confidence: 99%
“…The most commonly implicated regions have been left inferior frontal cortex, left superior temporal cortex, and left inferior parietal cortex, with many studies reporting one or more of these regions to be implicated in sentence-level comprehension (Amici et al, 2007; Dronkers, Wilkins, Van Valin, Redfern, & Jaeger, 2004; Fridriksson, Fillmore, Guo, & Rorden, 2015; Leff et al, 2009; Newhart et al, 2012; Rogalski et al, 2011; Teichmann et al, 2015; Thothathiri, Kimberg, & Schwartz, 2012; Wilson et al, 2011; Wilson, Galantucci, Tartaglia, & Gorno-Tempini, 2012). Some studies have suggested that specific regions within this network have specific functions, such as a role for inferior frontal cortex in processing syntactically complex sentences (Amici et al, 2007), and a role for the posterior superior temporal gyrus in auditory short-term memory in support of sentence comprehension (Leff et al, 2009; Wilson, Galantucci, Tartaglia, & Gorno-Tempini, 2012).…”
Section: Key Empirical Contributionsmentioning
confidence: 99%
“…Newhart et al (2012) studied 53 PWA with strokes on their first hospitalization day. They measured the size of infarction and hypoperfusion in Broca’s area (BA 44 and 45) and 12 other BAs (6, 10, 11,18, 19, 20, 21, 22, 37, 38, 39, 40) on a three point scale: (1) part, (2) all, or (0) none.…”
mentioning
confidence: 99%